Adoption of Smart Libraries Applications for Achieving Sustainable Development Goals (SDGS) in Nigeria Tertiary Institutions Libraries in Kaduna State - Dada, Kayode Sunday John; Mohammed, Hafsat Aliyu; Habibu, Mohammed (Information Research Communications, 2025)
Background/Purpose This study examines the adoption of smart library applications across eight (8) tertiary institution libraries in Kaduna State, Nigeria, based on 285 responses assessing eight technology types. Materials and Methods The study adopted a descriptive approach, through the quantitative methodology. Methodology adopted was descriptive cross-sectional survey design. The study used total enumeration sampling technique to select all librarians from Tertiary institutions in Kaduna State. The data collected were analyzed using descriptive statistics of Frequency Distribution Tables, Percentage, mean and standard deviation. For descriptive statistics on frequency and percentage distribution tables 50% was used as the benchmark for decision making using SPSS Statistical Package 23rd edition. Ethical approval was obtained from the Kaduna State University Institutional Review Board. Results/Findings The results reveal Mobile Applications and Self-Service Tools as the most adopted (15.44%, Mean=5.50, SD=3.25), followed by Automation and Cloud Computing Systems (15.09%, Mean=5.38, SD=2.26), indicating a focus on user accessibility and operational efficiency. Digital Media and Maker Tools (13.33%, Mean=4.75, SD=1.98) and AR/VR and 3D Navigation (12.28%, Mean=4.38, SD=2.07) also show significant uptake, enhancing user engagement. RFID Systems (11.23%, Mean=4.00, SD=0.76) and Software Defined Networking (SDN) and Big Data Analytics (11.58%, Mean=4.12, SD=1.81) are moderately adopted, while IoT Integration (10.88%, Mean=3.88, SD=2.36) and AI and Chatbots (10.18%, Mean=3.62, SD=2.07) lag, likely due to infrastructure and expertise constraints. Variability in adoption, particularly for Mobile Applications and IoT, suggests disparities in funding and technological readiness. Conclusion/Recommendation These findings show the transformative potential of smart technologies in aligning libraries with Nigeria’s Smart City Initiative and Sustainable Development Goals. The study recommends that Nigerian tertiary institutions in Kaduna State should prioritize AI and chatbot integration through staff training and partnerships to enhance user support and service personalization.
Keywords: AI Chatbots; Automation; IoT Integration; Mobile Applications; Smart Libraries.